Development of cost estimation models based on ANN ensembles and the SVM method - Juszczyk, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Cost estimation, as one of the key processes in construction projects, provides the basis for a number of project-related decisions. This paper presents some results of studies on the application of artificial intelligence and machine learning in cost estimation. The research developed three original models based either on ensembles of neural networks or on support vector machines for the cost prediction of the floor structural frames of buildings.
Keywords: construction cost estimation; cost modelling; ensemble of neural networks; support vector machines; koszty budowy; modelowanie kosztów; zespół sieci neuronowych